Impact of industry 4.0 on supply chain sustainability : current status and future pathways - Mathiyazhagan, M.; Kishore, Aakanksha; Behdani, Behzad; Thanki, Heena (Emerald Publishing Limited, 2024)
Global events such as the COVID-19 pandemic and war in Ukraine brought massive disruption to supply chains around the world, shining a light on the environmental impacts of such systems. What role can Industry 4.0 play in making supply chains sustainable and resilient? Industry 4.0 ushers in a new era of utilizing smart devices to tracing and optimizing resource usage, enabling repair, recycling, and re-use, potentially influencing sustainability in supply chains. Industry 4.0 supports the allocation of resources based on real-time data resulting in new sustainable practices. Scholars from around the world examine a range of Industry 4.0 factors and their impact on improving the sustainability of global supply chains in Impact of Industry 4.0 on Supply Chain Sustainability. The findings are useful for researchers and practitioners in a range of fields and roles looking to create strong logistic networks.